2022
DOI: 10.1016/j.beth.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training via a Mobile Application to Reduce Obsessive-Compulsive-Related Distress and Cognitions During the COVID-19 Outbreaks: A Randomized Controlled Trial Using a Subclinical Cohort

Abstract: Obsessive-compulsive disorder (OCD) is a persistent psychiatric disorder causing significant impairment in functioning. The COVID-19 pandemic has exacerbated OCD-related symptoms and interrupted access to treatment. Recent research suggests mHealth apps are promising tools for coping with OCD symptoms. This randomized controlled trial evaluated the effects of a CBT-based mobile application designed to reduce OCD symptoms and cognitions in community participants considered at high-risk of developing OCD symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…In general, for the adult population, Roncero et al [18,21] showed that daily cognitive training using the GGtude platform for OCD (OC and RO modules) decreases OCD-related maladaptive beliefs. Similarly, Cerea et al [22] and Akin-Sari et al [23], replicated these results in participants with subclinical levels of relationship-related-OCD symptoms and OCD symptoms, respectively. Findings also suggest that challenging maladaptive beliefs impacts OCD symptoms.…”
Section: Introductionmentioning
confidence: 79%
“…In general, for the adult population, Roncero et al [18,21] showed that daily cognitive training using the GGtude platform for OCD (OC and RO modules) decreases OCD-related maladaptive beliefs. Similarly, Cerea et al [22] and Akin-Sari et al [23], replicated these results in participants with subclinical levels of relationship-related-OCD symptoms and OCD symptoms, respectively. Findings also suggest that challenging maladaptive beliefs impacts OCD symptoms.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, using cross-over designs, Roncero et al (21) and Cerea et al (22) also observed reductions in OCD symptoms (using the Obsessive-Compulsive Inventory -Reduced; OCI-R) after the use of the app. In the same vein, Akin-Sari et al (23) reported a large reduction in the OCI-R scores of participants at risk of OCD, which could be attributable to the effect of the app, suggesting that the OC module could be a promising tool for early intervention in OCD. Finally, Pascual-Vera et al (24), provide evidence in favor of these assumptions in clinical samples.…”
mentioning
confidence: 93%
“…In the field of sleep disturbances, cognitive stimulation is expected to improve cognitive inhibition ability and thus reduce alertness and monitoring of disruptive stimuli during sleep. At the same time, reasoning capacity is strengthened, and the presence of arousing, anxious, worrying, or distressing thoughts is reduced [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%